2011
DOI: 10.3109/08916934.2011.604658
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of ZnT8 autoantibodies could help to screen latent autoimmune diabetes in adult-onset patients with type 2 phenotype

Abstract: Autoantibodies to zinc transporter 8 (ZnT8A) constitute an additional marker of autoimmune diabetes, complementing those already used in diagnosis support. ZnT8A could also be found in latent autoimmune diabetes of adults (LADA). The aim of this study was to evaluate the prevalence of ZnT8A in adult-onset diabetic patients in Argentinian population. A total of 271 patients diagnosed for diabetes at mean age 53.4 ± 10.9, body mass index ≤ 30, without insulin treatment for the first year of disease, and initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 18 publications
3
36
0
1
Order By: Relevance
“…Moreover, Trabucchi and cols. have shown that a significant proportion of autoimmune adult-onset diabetic patients present ZnT8A as the only humoral marker (32).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Trabucchi and cols. have shown that a significant proportion of autoimmune adult-onset diabetic patients present ZnT8A as the only humoral marker (32).…”
Section: Discussionmentioning
confidence: 99%
“…Adults (LADA). In a previous report (11,19) we have proved that patients with adult-onset DM initially identified as 'marker negative', based on GADA and IA-2A screening, were reclassified as autoantibody positive when tested for ZnT8A. In the present study, we have included homodimer ZnT8 probes in order to improve the differential characterization of ZnT8A in type 1 and non-obese adult-onset diabetic patients.…”
Section: Type1 Dm N=46mentioning
confidence: 99%
“…ZnT8A were assessed by radioligand binding assay (RBA) as previously described (11). Briefly, cDNA coding for ZnT8-Arg325, ZnT8-Trp325, ZnT8-Arg-Arg325, ZnT8-TrpTrp325, and ZnT8-Arg-Trp325 were transcribed and translated using a rabbit reticulocyte lysate system (Promega Corporation) and …”
Section: Radioligand Binding Assay Protocol For Znt8amentioning
confidence: 99%
See 2 more Smart Citations